Chorioretinitis in infants - Modrzejewska, Monika; Lachowicz, Ewelina; Karczewicz, Danuta; Zdanowska, Alicja (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The aim of this review is to present cases of chorioretinitis in infants caused by viral and parasitic infections. Material and methods: Four infants with viral chorioretinitis were identified in a routine ophthalmological examination. Laboratory tests towards bacterial, viral and parasitic diseases were performed. Results: Toxoplasmosis, rubella, and CMV infections were diagnosed in clinical and laboratory tests. After a wide spectrum of therapy a total remission of inflammatory process in all the discussed children was observed. Conclusions: Posterior uveitis is an ocular complication which can be connected with viral or parasitic infections in postnatal period. Prematurity, normal delivery, intrauterine transmission, breast feeding, comorbid diseases might be associated with chorioretinitis in infants.